Effects of an experimental terrestrial runoff on the components of the plankton food web in a Mediterranean coastal lagoon - Courboulès, Justine; Vidussi, Francesca; Soulié, Tanguy; Nikiforakis, Eftihis; Heydon, Marie; Mas, Sébastien; Joux, Fabien; Mostajir, Behzad (Frontiers in Marine Science, 2023)
The Mediterranean region is undergoing an increase in the frequency and intensity of extreme rainfall events, resulting in terrestrial runoffs that can affect aquatic environments in coastal regions. The goal of this study was to investigate the effects of terrestrial runoff on natural coastal planktonic assemblages. For this purpose, an in situ mesocosm experiment was conducted in May 2021 in the Mediterranean Thau Lagoon. A terrestrial runoff event was simulated in duplicate mesocosms by adding natural forest soil that was left to maturate naturally for two weeks in river water. After the addition of maturated soil, the abundance and diversity within the planktonic food web, from viruses to metazooplankton, were monitored for 18 days. The addition of maturated soil to the terrestrial runoff treatment greatly depressed the light availability in the mesocosms and potentially enhanced flocculation and sedimentation in the mesocosms, resulting in an immediate negative effect on phytoplankton, decreasing the chlorophyll-a (Chl-a) concentration by 70% for 12 days. Afterward, remineralized nutrient in the terrestrial runoff treatment induced a subsequent positive effect on phytoplankton, which resulted in a diatom bloom and an increase in picophytoplankton and cyanobacteria abundance toward the end of the experiment. Overall, the Chl-a concentration was 30% lower in the terrestrial runoff treatment over the 18 days of experiment, whereas bacteria were 15% more abundant than in the control. This suggests that over the course of the experiment, the addition of maturated soil favoured bacteria instead of phytoplankton at the base of the planktonic food web. The addition of the maturated soil was detrimental for all protozooplankton groups and mixotrophic dinoflagellates, but seemed to favour metazooplankton, notably mollusk larvae, copepod nauplii, and rotifers. This implies that in the terrestrial runoff treatment, the preferential pathway for biomass transfer was through the direct consumption of bacteria and/or phytoplankton by metazooplankton. Therefore, in Thau Lagoon, after a terrestrial runoff, the transfer of biomass within the planktonic food web would potentially be more efficient by promoting direct transfer from the base to the top of the food web, subsiding intermediate trophic levels such as protozooplankton.